International human rights law and destitution: an economic, social and cultural rights perspective - Graham, Luke D. (Routledge research in human rights law, 2023)
Conceptualising destitution -- The level of rights realisation required to avoid destitution -- The rights required to avoid destitution -- Austerity : the context of rising destitution in the United Kingdom -- Economic, social and cultural rights and destitution in the United Kingdom -- Addressing destitution in the United Kingdom using economic, social and cultural rights.